1995
DOI: 10.1016/0895-7061(94)00184-d
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin I converting enzyme (ACE) gene polymorphism and essential hypertension in JapanEthnic difference of ACE genotype

Abstract: A polymorphism of the angiotensin I converting enzyme (ACE) gene has recently been reported and analysis of this polymorphism has indicated that it is associated with several cardiovascular diseases. However, the results are still controversial and such association has not yet been established conclusively. To determine whether the ACE gene may be responsible for essential hypertension in a Japanese population, we also compared the distribution of genotypes and the allele frequency of this polymorphism in our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
24
2
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 12 publications
10
24
2
1
Order By: Relevance
“…Gu et al (1994) also reported a lack of association between the I/D polymorphism in a hypertensive Belgian population (n = 119) compared with controls, regardless of age or sex. In Japanese patients with essential hypertension, Ishigami et al (1995) reported that there was no association with ACE I/D polymorphism. Barley et al (1996) suggested that there may be racial differences in the association of ACE I/D polymorphism with hypertension in that subjects of European descent showed no association between ACE genotype and blood pressure, whereas subjects of African Carribean descent did.…”
Section: Angiotensin-converting Enzyme Insertion/ Deletion Polymentioning
confidence: 99%
“…Gu et al (1994) also reported a lack of association between the I/D polymorphism in a hypertensive Belgian population (n = 119) compared with controls, regardless of age or sex. In Japanese patients with essential hypertension, Ishigami et al (1995) reported that there was no association with ACE I/D polymorphism. Barley et al (1996) suggested that there may be racial differences in the association of ACE I/D polymorphism with hypertension in that subjects of European descent showed no association between ACE genotype and blood pressure, whereas subjects of African Carribean descent did.…”
Section: Angiotensin-converting Enzyme Insertion/ Deletion Polymentioning
confidence: 99%
“…21 Although only one study, 18 but not others 15,16,19 including this study, reported the association between this polymorphism and patients with essential hypertension, recent reports 11 suggested that this polymorphism may be associated with salt sensitivity. They found increased II genotype in salt-sensitive hypertension.…”
Section: =0427)mentioning
confidence: 99%
“…The ACE genotype was determined by the PCR technique according to the method of Rigat et al 14 with minor modifications. 15 PCR products were analysed by 1.6% agarose gel electrophoresis and visualised with ethidium bromide staining for allele identification. A 490 bp fragment (in the presence of the insertion allele) and a 190 bp fragment (in the absence of the insertion allele) were identified.…”
Section: Polymerase Chain Reaction (Pcr) Of Ace Gene Polymorphismmentioning
confidence: 99%
“…Efforts to establish an association between essential hypertension and the ACE gene I/D polymorphism have been undertaken in different human populations, sometimes with negative results (Harrap et al 1993;Higashimori et al 1993;Schmidt et al 1993;Ishigami et al 1995a), although others have described a positive correlation (Zee et al 1992;Morris et al 1994). The results of some of these studies suggest that the effect of the ACE polymorphism in the etiology of hypertension may vary according to whether patients are classified by sex, race, or age.…”
Section: Introductionmentioning
confidence: 88%